35 pioneer graduates of UMP and AKEPT collaboration programme in talent development - UMP, PNC (2019)
A total of 35 graduands for the collaboration programme between Universiti Malaysia Pahang (UMP) and Higher Education Leadership Academy (AKEPT), Ministry of Education Malaysia (MOE) received their diploma from the Vice-Chancellor of UMP, Professor Ir. Dr. Wan Azhar Wan Yusoff on the second day of the UMP’s 14th Convocation Ceremony on 17 November 2019 at the UMP’s Sports Complex Gambang Campus.